Media Archaeology as Practice: The case of Bill Morrison's Dawson City: Frozen Time (International Journal on Stereo & Immersive Media, 2019)
Bill Morrison’s film Dawson City: Frozen Time (2016) is about a famous story among archivists: in 1978, 533 nitrate film reels, mostly from the 1910s, were discovered in what used to be a swimming pool in a remote city in Canada. Many of these films were thought to be completely lost, and the Dawson City Film Find remain the only surviving prints to date.  This paper will expose Morrison’s work as media archaeology practice, connected to media archaeology’s main thematic thread histories of the present. Morrison explores the Dawson City story as motive for a reflection on historical and material time. Erkki Huhtamo’s topos approach will be used as the framework for the analysis of Morrison’s treatment of history; and Vivian Sobchack’s conditions for experiencing the past as “presence” will inform the analysis regarding the importance of the film materiality. Finally, Eelco Runia’s thoughts on metonymic and metaphorical devices will inform the connection between history and presence.